THE POSITION OF INDUSTRY IN THE ECONOMY: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
World practice shows that in order to achieve dynamic rates of economic development, industry plays a decisive role as the fundamental basis of the entire national economy. Economic periods are distinguished not by what is produced, but by the means of labor directly related to the industry that creates or uses this technique. At the current stage of development, one of the strategic tasks of the economic policy of Uzbekistan should be the effective development of the country's industry, which allows to accelerate the pace of development of the national economy. which ultimately leads to an increase in the quality of life of the country's population.